Challenges and Social Adaptation Faced by Orthodox Students in Roman Catholic School - Winin Maulidya Saffanah; Faizah Ulumi Firdausi; Paulus Sujianto (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
Orthodox are a minority group within the minority in Indonesia. Some of theseOrthodox believers have identity as Christian or Catholic, which is also minorityreligions in Indonesia. The adjustments or adaptations made by Orthodox, especially those currently in school, are very interesting and important to learn. For Orthodox students in Malang, the absence of special religious lessons and their status as Christians make them face challenges, especially when studying at Catholic schools. The approach used in this research is qualitative. In particular, the researchers also used a phenomenological perspective in understanding adaptation in this school of Orthodox students. The informant in this study were students who believe in Orthodox and live in Malang. In general, there are no major problems that cause students to clash with other students or schools. Even so, there are problems in the matters of religious ordinances, the sign of the cross, and explaining their status as Orthodoxs. In general, the adaptation happened smoothly because these students were able to suppress their identity as Orthodox followers in the school environment. In addition, the absence of religious instruction in schools can be overcome by religious lessons in the Orthodox church.